Education of parents in Pavlik harness application for developmental dysplasia of the hip using a validated simulated learning module - Gargan, Kate E. (J Child Orthop, 2016)
BACKGROUND: The Pavlik harness is the most common initial treatment for developmental dysplasia of the hip worldwide. During treatment, parents are required to re-apply the harness at home. Teaching parents how to apply the harness is therefore paramount to success. While simulated learning for medical training is commonplace, it has not yet been trialed in teaching parents how to apply a Pavlik harness. METHODS: A group of parents underwent a simulated learning module for Pavlik harness application. Parents were evaluated pre- and post-exposure and at one month after testing. A validated objective structured assessment of technical skill (OSATS) and a global rating scale (GRS) specific to Pavlik harness application were used for evaluation. A control group of parents was also tested at both time points. A clinical expert group was used to determine competency. ANOVA and t tests were used to assess differences between groups and over time. RESULTS: Parent scores on the OSATS improved to the level of expert clinicians both immediately post-intervention and at retention testing. However, on the GRS, only half were considered competent due to their inability to achieve the required hip positions. The control group did not improve nor were they considered competent. CONCLUSIONS: The use of a simulated learning module improves both the confidence and skill level of parents in the application of the Pavlik harness. However, the challenges parents face in understanding the more detailed subtleties of medical care suggest that they still require an appropriate level of supervision by clinicians to ensure effective treatment. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11832-016-0751-7) contains supplementary material, which is available to authorized users.